The impact of perfectionism traits on perceived team cohesion of futsal players - Nascimento Junior, José Roberto Andrade; Freire, Gabriel Lucas Morais; Moreira, Caio Rosa; Codonhato, Renan; Oliveira, Daniel Vicentini de; Fortes, Leonardo de Sousa; Fiorese, Lenamar (Cuadernos de Psicología del Deporte, 2022)
This cross-sectional study was to investigate the relationship between the traits of perfectionism and the perception of group cohesion in futsal athletes. 301 athletes from the 2013 National Futsal League participated with an average age of 25.48 ± 4.90 years. The instruments were: Multidimensional Perfectionism Scale for Sport-2 and the Group Environment Questionnaire. For analysis, it was conducted using the Kolmogorov-Smirnov, MANOVA, Pearson correlation and Multiple Regression tests (p<0,05). The results showed that the traits of adaptive perfectionism positively predicted social cohesion for unclassified athletes. Meanwhile, the perfectionist concerns traits of poorly adaptive perfectionism can negatively predict social and task cohesion, with the exception of “perceived parental pressure” which showed a positive prediction in all groups of athletes for social and task cohesion. Unclassified athletes had a higher perception of cohesion for the task, while reserves had a higher perception of social aspects. Thus, we can conclude that there is a positive relationship between adaptive perfectionism and the perception of social cohesion in unclassified athletes, in addition to a negative relationship between the dimensions of poorly adaptive perfectionism and group cohesion.